2015
DOI: 10.7314/apjcp.2015.16.5.1751
|View full text |Cite
|
Sign up to set email alerts
|

The Carcinogenic Liver Fluke Opisthorchis viverrini is a Reservoir for Species of Helicobacter

Abstract: There has been a strong, positive correlation between opisthorchiasis-associated cholangiocarcinoma and infection with Helicobacter. Here a rodent model of human infection with Opisthorchis viverrini was utilized to further investigate relationships of apparent co-infections with O. viverrini and H. pylori. A total of 150 hamsters were assigned to five groups: i) Control hamsters not infected with O. viverrini; ii) O. viverrini-infected hamsters; iii) non-O. viverrini infected hamsters treated with antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 43 publications
5
59
0
2
Order By: Relevance
“…In hamsters infected with O. viverrini alone, H. pylori was detected in 50% of the gastric tissues tested but was less prevalent in the hepatobiliary system (25%) than in the HP group, suggesting that oral inoculation with H. pylori permits its transmission to the biliary system with or without the presence of flukes. There appears to be a background level of natural infection of gastric tissue (but not liver tissue) with H. pylori in our hamsters, which was similar to findings in a previously study (11,28). Inoculation with additional H. pylori and/or the presence of worms was associated with the presence of H. pylori in the biliary system.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In hamsters infected with O. viverrini alone, H. pylori was detected in 50% of the gastric tissues tested but was less prevalent in the hepatobiliary system (25%) than in the HP group, suggesting that oral inoculation with H. pylori permits its transmission to the biliary system with or without the presence of flukes. There appears to be a background level of natural infection of gastric tissue (but not liver tissue) with H. pylori in our hamsters, which was similar to findings in a previously study (11,28). Inoculation with additional H. pylori and/or the presence of worms was associated with the presence of H. pylori in the biliary system.…”
Section: Discussionsupporting
confidence: 79%
“…The first is by causing gastric injury, facilitating transport to the liver via the bloodstream (29). Second, when inoculated with O. viverrini, H. pylori may be carried into the hepatobiliary system directly by the worms (11). Third, physical obstruction of the bile ducts by O. viverrini infection (30) may lead to increased pressure and a low pH within the biliary tract, which might permit influx of H. pylori from the gastrointestinal tract into the hepatobiliary system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previously published data showed that cagPAI especially cagA of H. pylori can induce inflammation and disturbance of cell kinetic on hepatobiliary cell lines [31,36,37]. Therefore, we suggest that, in addition to O. viverrini infection, H. pylori may be a co-factor of the O. viverrini pathogenesis in Thai CCA patients as previously described by our colleagues, showing the significant relationship between O. viverrini and H. pylori [38]. However, the association and role of H. pylori in CCA should be further investigated.…”
Section: Discussionsupporting
confidence: 51%
“…(65) . O. viverrini infection may also cause changes in bile acid composition that reduce alkalinity which may allow for easier colonisation of H. pylori (66,67) , and may even directly contribute to biliary inflammation (68) .…”
Section: Cholangiocarcinomamentioning
confidence: 99%